Faktor-Faktor yang Mempengaruhi Personal Hygiene Pedagang Daging dan Sanitasi Lingkungan pada Tempat Berjualan Daging di Pasar Mambal Desa Mambal, Abiansemal - I Gusti Ayu Putu Dian Anggraeni; Ni Putu Widya Astuti; Ni Luh Utari Sumadewi (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Meat traders in Mambal Market of Mambal Abiansemal Village still do not fulfill the requirement, because of their location are close to vegetable and daily goods traders, so that it affect the sur-rounding odor as well as the air circulation that inhaled by traders and buyers. The aim of this study was to identify factors related with hygiene and sanitation of the meat shops in Mambal Market. The study was a cross sectional design with questionnaire and observation as the data instruments. Based on the results, factors that are related with hygiene and sanitation of the meat shops are: personal hygiene (p-value 0,024), equipment and facilities (p value 0,001), sewerage system (p value 0,001), and meat cutter devices (p value 0,001). Factors which are identified corresponding with personal hygiene and the sanitation of meat shops are: traders do not wear personal protective devices, wear rings and smoke while working, and open sewerage system and no hand-washing facility provided.